Expatriate Women in Saudi Arabia: Challenges and Transformations in the Migration Process - Akl Moanack, Paola María; Docal Millán, María del Carmen; Joya Rozo, Mayra Alejandra; Fernández Moreno, Mary Luz (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
The expatriation of Latinos as one of the modalities of migration has impacted women and their family dynamics. Objective: To deepen, from the voices of women, the transformations in family dynamics and gender roles during migration and integration to the sociocultural context. Methodology: Descriptive, mixed, cross-sectional study, through questionnaire and interview. 103 expatriate Latina women in Saudi Arabia, sampled by convenience with snowball technique. Results: They report changes in roles within the family, asymmetry in gender relations and difficulties in assimilation to Islamic culture. Conclusions: the migration process generates adaptation challenges and opportunities that promote personal development and quality of family life.